Use of a urea-based ionic liquid in the regulation of elastomer elasticity

CN116925523BActive Publication Date: 2026-10-27SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310857177.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2026-10-27
Estimated Expiration
2043-07-13

AI Technical Summary

Benefits of technology

[0035]本发明将功能化的离子液体加入多种弹性体中,离子液体的功能基团脲基含有多个可形成氢键的位点,多种弹性体的特征基团(如氨基甲酸酯、酰胺、酯基)同样有多个可形成氢键的位点,故两者之间可形成多重氢键,通过氢键耦合作用增强分子间作用力,增强弹性体的刚性,降低弹性,故而可以根据离子液体的添加量来自由调控多种弹性体的弹性,以适应材料的使用需求。经本发明改性后的多种弹性体能够用于服装领域的弹性纤维、汽车领域的密封圈等。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116925523B_ABST
    Figure CN116925523B_ABST
Patent Text Reader

Abstract

The application discloses application of a urea group-containing ionic liquid in regulating elasticity of an elastomer, wherein the cation of the urea group-containing ionic liquid is imidazolium and contains a urea group, and the anion is a halogen anion; and the elastomer includes polyurethane elastomer, polyamide elastomer and polyester elastomer. The application regulates elasticity by adding different proportions of the urea group-containing ionic liquid into various elastomers, and the principle is that the functional group urea group of the ionic liquid contains multiple hydrogen-bonding sites, the characteristic groups of various elastomers also have multiple hydrogen-bonding sites, so multiple hydrogen bonds can be formed between the two, and the hydrogen bond coupling effect can enhance the intermolecular force, thereby enhancing the rigidity of the elastomer and reducing the elasticity, and thus the elasticity of various elastomers can be freely regulated according to the addition amount of the ionic liquid to adapt to the use requirements of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer modification technology, specifically relating to the application of a urea-containing ionic liquid in regulating the elasticity of elastomers. Background Technology

[0002] Polyurethane elastomers are a versatile and emerging organic polymer material, often referred to as the fifth largest plastic. They are typically produced by reacting oligomeric polyols, polyisocyanates, and chain extenders / crosslinking agents. Belonging to the block polymer family, they consist of "soft segments" and "hard segments." The hard segments (derived from isocyanates and chain extenders) are dispersed within the soft segment phase (derived from oligomeric polyols), acting as physical crosslinking points. Therefore, compared to other synthetic rubbers, polyurethane elastomers exhibit superior strength and abrasion resistance, maintaining high elongation even at high hardness. Their applications are extensive, encompassing cold chain logistics, transportation, construction, home furnishings, clothing and footwear, machinery parts, food, packaging and printing, sporting goods, and defense.

[0003] Polyamide elastomers consist of high-melting-point crystalline hard segments (polyamide) and amorphous soft segments (polyester or polyether). Hard segments can be made of polycaprolactam 6, polyamide 66, polydodecanoic acid, aromatic polyamides, etc., while soft segments can be made of polyethylene glycol, polypropylene glycol, polybutane glycol, hydroxyl-terminated aliphatic polyesters, etc. Their properties depend on the type of hard segment and the lengths of the two segments. Polyamide elastomers possess excellent toughness, chemical resistance, abrasion resistance, and sound absorption properties, making them widely used in various fields such as automotive parts, sporting goods, medical supplies, household goods, machine tools, toys, and electronics and electrical products.

[0004] Polyester elastomers, also known as polyester rubber, are linear block copolymers containing polybutylene terephthalate (PET) hard segments and aliphatic polyester or polyether soft segments. They combine the excellent elasticity of rubber with the easy processability of thermoplastics, offering adjustable hardness and design flexibility, making them a promising new variety of thermoplastic elastomers. Compared to rubber, polyester elastomers offer better processability and a longer service life; compared to engineering plastics, they also possess high strength, while exhibiting better flexibility and dynamic mechanical properties. Polyester elastomers possess outstanding mechanical strength, excellent resilience, and a wide operating temperature range, leading to their widespread application in automotive parts, hydraulic hoses, cables and wires, electronics, industrial products, sporting goods, and biomaterials. Their application is most extensive in the automotive industry, accounting for over 70% of all applications.

[0005] Ionic liquids are salts composed entirely of cations and anions that are liquid at or near room temperature; they are also known as low-temperature molten salts (<100℃). Since the mid-1990s, ionic liquids have gradually attracted the attention of the chemical and materials science communities. In just over a decade, their applications have expanded from organic synthesis, inorganic synthesis, and catalysis to materials science, environmental science, and analytical testing. They are generally composed of organic cations and inorganic or organic anions. Common cations include quaternary ammonium salts, quaternary phosphonium salts, imidazole salts, and pyrrole salts, while anions include halide ions, tetrafluoroborate ions, and hexafluorophosphate ions. Theoretically, there may be one trillion types of ionic liquids. Currently, the cations in ionic liquids under study are mainly imidazole cations, and the anions are mainly halide ions and other inorganic acid ions (such as tetrafluoroborate). Ionic liquids possess advantages such as conductivity, low volatility, non-flammability, electrochemical stability, and a wide potential window, leading to their widespread use in organic synthesis, separation and purification, and electrochemistry.

[0006] The vitality of ionic liquids lies in their inherent "designability." Many properties of ionic liquids, such as melting point, viscosity, density, and solubility, can be adjusted by modifying their structure. Therefore, specific organic functional groups can be introduced onto the cations or anions of ionic liquids, allowing for the design and synthesis of "functionalized" ionic liquids with unique structures according to different reaction requirements. For example, alkenyl, carboxyl, acid, and cyano functional groups can be introduced onto the cations. The urea group, with its multiple hydrogen bonding sites, is a unique functional group; by utilizing the designability of ionic liquids, its introduction can unlock new properties of ionic liquids. Summary of the Invention

[0007] The purpose of this invention is to provide an application of urea-containing ionic liquids in regulating the elasticity of elastomers. Urea groups possess multiple hydrogen bonding sites and are unique functional groups. Taking advantage of the designability of ionic liquids, these groups can be introduced. When elastomers contain urethane, amide, or ester groups, these groups also contain multiple hydrogen bonding sites. The advantage of these groups having multiple hydrogen bonding sites can be utilized to form multiple hydrogen bonds with the urea groups to modify the elastomer. Through hydrogen bonding coupling, intermolecular forces are enhanced, elasticity is reduced, and modulus is increased. This allows for free control of the hardness and softness of various elastomers, significantly altering their elasticity to meet the application requirements of materials.

[0008] The objective of this invention is achieved through the following technical solution:

[0009] The application of a urea-containing ionic liquid in regulating the elasticity of elastomers, wherein the cation of the urea-containing ionic liquid is imidazolium containing a urea group, and the anion is a halide anion.

[0010] Furthermore, the urea-containing ionic liquid has the structure shown in formula (I):

[0011]

[0012] In formula (I), the cation is imidazolium and contains a urea group, where n and m are integers, and 1≤n≤4, 0≤m≤8; the anion X - Selected from Cl - ,Br - I - .

[0013] Furthermore, the elastomer includes polyurethane elastomers, polyamide elastomers, and polyester elastomers.

[0014] Furthermore, the urea-containing ionic liquid is prepared by the following method:

[0015] Solution A is obtained by dispersing imidazole compounds containing terminal amino groups in a solvent;

[0016] Solution B is obtained by dispersing monoisocyanate compounds in a solvent;

[0017] Solution B is slowly added dropwise to solution A at a constant rate under nitrogen or inert gas atmosphere at 10–40℃. After the addition is complete, the mixture is sealed and reacted for 4–24 hours to obtain a mixture of urea-containing imidazole compounds.

[0018] Under nitrogen or inert gas atmosphere at 0–10 °C, a haloalkane is added to the generated mixture of urea-containing imidazole compounds, and the reaction is carried out in a closed system for 24–48 h to obtain the urea-containing ionic liquid.

[0019] Further, the solvent is at least one selected from acetonitrile, dichloromethane, chloroform, N,N-dimethylformamide, and N,N-dimethyl sulfoxide;

[0020] The molar ratio of the imidazole compound containing the terminal amino group to the monoisocyanate compound is (0.1-0.3):(0.15-1.5);

[0021] The dripping time is 0.5–2 hours;

[0022] The molar ratio of the imidazole compound containing the terminal amino group to the monohaloalkane is (0.1-0.3):(0.2-0.6).

[0023] Furthermore, the present invention regulates the elasticity of the elastomer through the following steps:

[0024] Step 1: Add the urea-containing ionic liquid to the prepolymer of the elastomer and stir to obtain a mixed solution;

[0025] or

[0026] The elastomer is dissolved in a solvent, and then an ionic liquid containing urea groups is added and stirred to obtain a mixed solution;

[0027] Step 2: Sonicate the mixed solution obtained in step S1;

[0028] Step 3: Pour the ultrasonically treated mixture from step S2 into the mold, and then heat it with a blower.

[0029] Furthermore, the amount of the urea-containing ionic liquid added can be adjusted according to needs, including but not limited to 0.1–5 wt% of the elastomer. The amount of ionic liquid added can be freely controlled as needed, and the modulus and elongation at break of the elastomer will change accordingly with the change in the amount of ionic liquid added.

[0030] Furthermore, the stirring speed is 50–200 rpm, and the stirring time is 24–48 h.

[0031] Further, the solvent is at least one selected from N,N-dimethylformamide, butanone, cyclohexanone, acetone, ethyl acetate, toluene, methanol, ethylene glycol, hexafluoroisopropanol, m-cresol, and phenol.

[0032] Furthermore, the ultrasonic treatment time is 1 to 4 hours, and the ultrasonic treatment is to ensure uniform mixing.

[0033] Furthermore, the temperature of the blower heating is 60–120°C, and the time is 24–72 hours, in order to remove the solvent.

[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0035] This invention incorporates functionalized ionic liquids into various elastomers. The urea group, a functional group in the ionic liquid, contains multiple sites for hydrogen bonding. Similarly, the characteristic groups of the various elastomers (such as urethane, amide, and ester groups) also have multiple hydrogen bonding sites. Therefore, multiple hydrogen bonds can form between the two, enhancing intermolecular forces through hydrogen bonding coupling, thereby increasing the rigidity of the elastomer and reducing its elasticity. Thus, the elasticity of various elastomers can be freely adjusted according to the amount of ionic liquid added to meet the application requirements of the materials. The various elastomers modified by this invention can be used in elastic fibers in the clothing industry and sealing rings in the automotive industry. Attached Figure Description

[0036] Figure 1 The image shows the 1H NMR spectrum of the urea-containing ionic liquid synthesized in Example 1.

[0037] Figure 2 The image shows the infrared spectrum of the urea-containing ionic liquid synthesized in Example 1. Detailed Implementation

[0038] The following embodiments are provided to further illustrate the present invention, but are not intended to limit the invention. It should be noted that the embodiments are only for further illustration and should not be construed as limiting the scope of protection of the present invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make some non-essential improvements and adjustments based on the above description of the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0039] All raw materials involved in this invention can be purchased directly from the market. For process parameters not specifically specified, conventional techniques can be used as a reference.

[0040] In the examples, the elastomer modified with ionic liquid was cut into dumbbell-shaped specimens using a 4*50mm dumbbell-shaped cutter, and then tensile tests were performed to obtain tensile strength, Young's modulus, and elongation at break.

[0041] Example 1

[0042] I. Synthesis of Urea-Containing Ionic Liquids

[0043] Step 1: Disperse 75 mmol of 1-(3-aminopropyl)imidazolium uniformly in 300 ml of acetonitrile and then add it to a flask; disperse 112.5 mmol of n-butyl isocyanate uniformly in 100 ml of acetonitrile and then add it to a dropping funnel. Under nitrogen atmosphere at 25 °C, slowly and continuously add the acetonitrile solution from the funnel to the flask. After 1 hour, the addition is completed. Finally, seal the flask and react for 4 hours to allow the reaction to proceed fully, thus obtaining an acetonitrile solution of urea-containing imidazolium compounds.

[0044] Step 2: Under a nitrogen atmosphere at 0°C, add 150 mmol of iodomethane to the acetonitrile solution of the urea-containing imidazole compound obtained in Step 1. Seal the reactor and react for 24 hours. After that, remove the reaction solution, distill under reduced pressure at 60°C, and then wash repeatedly with toluene to obtain the urea-containing imidazole iodide salt (i.e., the urea-containing ionic liquid) shown in the following formula:

[0045]

[0046] In the formula, n = 3, m = 4, X = 1, the product yield is 66%, and its 1H NMR spectrum is as follows: Figure 1 As shown, the infrared spectrum is as follows Figure 2 As shown.

[0047] II. Urea-containing ionic liquids are used to modulate the elasticity of elastomers.

[0048] 0.1 wt% of the urea-containing imidazole iodide salt prepared above was added to a polyurethane solution (i.e., a polyurethane prepolymer synthesized from polyol, isocyanate, and chain extender) to obtain a polyurethane mixed solution. The solution was then mechanically stirred at 100 rpm for 48 hours, followed by ultrasonic mixing for 1 hour. The solution was then poured into a rectangular mold and dried at 80°C for 48 hours to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 3.65 MPa, Young's modulus 4.55 MPa, and elongation at break 1227%.

[0049] Example 2

[0050] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. 0.5 wt% of the prepared urea-containing imidazolium iodide was added to a polyurethane mixed solution (same as in Example 1), mechanically stirred at 100 rpm for 48 h, and then ultrasonically mixed for 1 h. The solution was then poured into a rectangular mold and dried at 80°C for 48 h to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 4.03 MPa, Young's modulus 4.89 MPa, and elongation at break 1158%.

[0051] Example 3

[0052] In this embodiment, urea-containing imidazole iodide (n=3, m=4) was synthesized using the same method as in Example 1. 1.0 wt% of the prepared urea-containing imidazole iodide was added to a polyurethane mixed solution (same as in Example 1), mechanically stirred at 100 rpm for 48 h, and then ultrasonically mixed for 1 h. The solution was then poured into a rectangular mold and dried at 80°C for 48 h to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 4.81 MPa, Young's modulus 5.42 MPa, and elongation at break 964%.

[0053] Example 4

[0054] In this embodiment, urea-containing imidazole iodide (n=3, m=4) was synthesized using the same method as in Example 1. 2.0 wt% of the prepared urea-containing imidazole iodide was added to a polyurethane mixed solution (same as in Example 1), mechanically stirred at 100 rpm for 48 h, and then ultrasonically mixed for 1 h. The solution was then poured into a rectangular mold and dried at 80°C for 48 h to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 5.36 MPa, Young's modulus 5.94 MPa, and elongation at break 799%.

[0055] Example 5

[0056] In this embodiment, urea-containing imidazole iodide (n=3, m=4) was synthesized using the same method as in Example 1. 3.0 wt% of the prepared urea-containing imidazole iodide was added to a polyurethane mixed solution (same as in Example 1), mechanically stirred at 100 rpm for 48 h, and then ultrasonically mixed for 1 h. The solution was then poured into a rectangular mold and dried at 80°C for 48 h to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 6.15 MPa, Young's modulus 6.67 MPa, and elongation at break 705%.

[0057] Example 6

[0058] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. 4.0 wt% of the prepared urea-containing imidazolium iodide was added to a polyurethane mixed solution (same as in Example 1), mechanically stirred at 100 rpm for 48 h, and then ultrasonically mixed for 1 h. The solution was then poured into a rectangular mold and dried at 80°C for 48 h to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 7.08 MPa, Young's modulus 7.35 MPa, and elongation at break 634%.

[0059] Example 7

[0060] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. 5.0 wt% of the prepared urea-containing imidazolium iodide was added to a polyurethane mixed solution (same as in Example 1), mechanically stirred at 100 rpm for 48 h, and then ultrasonically mixed for 1 h. The solution was then poured into a rectangular mold and dried at 80°C for 48 h to obtain the modified polyurethane elastomer. Tensile testing of the modified polyurethane elastomer yielded the following results: tensile strength 8.15 MPa, Young's modulus 8.03 MPa, and elongation at break 517%.

[0061] Comparative Example 1

[0062] This comparative example does not modify the polyurethane elastomer by incorporating ionic liquids. Instead, a uniform polyurethane mixture solution (same as in Example 1) is directly poured into a rectangular mold and baked at 80°C for 48 hours. The polyurethane elastomer is then cut into dumbbell-shaped specimens using a 4*50mm dumbbell-shaped cutter, and tensile tests are performed. The results are: tensile strength 3.37MPa, Young's modulus 4.34MPa, and elongation at break 1378%.

[0063] Example 8

[0064] In this embodiment, urea-containing imidazole iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon (i.e., polyamide) elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 0.1 wt% (relative to the nylon elastomer) of urea-containing imidazole iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 22.35 MPa, Young's modulus 12.94 MPa, and elongation at break 483%.

[0065] Example 9

[0066] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 0.5 wt% (relative to the nylon elastomer) of urea-containing imidazolium iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 27.66 MPa, Young's modulus 15.39 MPa, and elongation at break 382%.

[0067] Example 10

[0068] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 1.0 wt% (relative to the nylon elastomer) of urea-containing imidazolium iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 35.48 MPa, Young's modulus 17.98 MPa, and elongation at break 310%.

[0069] Example 11

[0070] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 2.0 wt% (relative to the nylon elastomer) of urea-containing imidazolium iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 38.37 MPa, Young's modulus 19.29 MPa, and elongation at break 256%.

[0071] Example 12

[0072] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 3.0 wt% (relative to the nylon elastomer) of urea-containing imidazolium iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 45.67 MPa, Young's modulus 24.15 MPa, and elongation at break 197%.

[0073] Example 13

[0074] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 4.0 wt% (relative to the nylon elastomer) of urea-containing imidazolium iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 50.38 MPa, Young's modulus 30.87 MPa, and elongation at break 143%.

[0075] Example 14

[0076] In this embodiment, urea-containing imidazolium iodide (n=3, m=4) was synthesized using the same method as in Example 1. Then, nylon elastomer was dissolved in hexafluoroisopropanol to obtain a hexafluoroisopropanol solution of the nylon elastomer. 5.0 wt% (relative to the nylon elastomer) of urea-containing imidazolium iodide was added to the hexafluoroisopropanol solution of the nylon elastomer, and the mixture was mechanically stirred at 100 rpm for 24 hours, followed by ultrasonic mixing for 1 hour. The solution was then injected into a rectangular mold and dried at 60°C for 24 hours to obtain the modified nylon elastomer. Tensile testing of the modified nylon elastomer yielded the following results: tensile strength 66.48 MPa, Young's modulus 37.58 MPa, and elongation at break 113%.

[0077] Comparative Example 2

[0078] This comparative example does not involve modifying the nylon elastomer with ionic liquid. Instead, a uniform hexafluoroisopropanol solution of the nylon elastomer (same as in Example 8) is directly injected into a rectangular mold and dried at 60°C for 24 hours. The nylon elastomer is then cut into dumbbell-shaped specimens using a 4*50mm dumbbell-shaped cutter, and tensile tests are performed. The results are: tensile strength 19.65MPa, Young's modulus 9.43MPa, and elongation at break 634%.

[0079] Table 1. Tensile test results of Examples 1-7 and Comparative Example 1

[0080]

[0081] Table 2 Tensile test results of Examples 8-14 and Comparative Example 2

[0082]

[0083] As shown in Tables 1 and 2, with the increase of the amount of ionic liquid added, the tensile strength and Young's modulus both increase, while the elongation at break decreases. This means that the rigidity of the material increases and the elasticity decreases. This indicates that the urea-containing ionic liquid of the present invention can freely control the elasticity of various elastomers by adjusting the amount added, so as to meet the application requirements of the material.

[0084] The above description, in conjunction with specific embodiments, provides a further detailed explanation of this application and should not be construed as limiting the specific implementation of this application to these descriptions. Those skilled in the art to which this application pertains can make several simple deductions or substitutions without departing from the concept of this application.

Claims

1. The application of a urea-containing ionic liquid in regulating the elasticity of elastomers, characterized in that, The cation of the urea-containing ionic liquid is an imidazolium urea-containing compound, and the anion is a halide anion; The urea-containing ionic liquid has the structure shown in formula (I): , (I), The elastomer includes polyurethane elastomers, polyamide elastomers, and polyester elastomers; The amount of the urea-containing ionic liquid added is 0.1 to 5 wt% of the elastomer.

2. The application of the urea-containing ionic liquid according to claim 1 in regulating the elasticity of elastomers, characterized in that, The urea-containing ionic liquid is prepared by the following method: Solution A is obtained by dispersing imidazole compounds containing terminal amino groups in a solvent; Solution B is obtained by dispersing monoisocyanate compounds in a solvent; Solution B is slowly added dropwise to solution A at a constant rate under nitrogen or inert gas atmosphere at 10~40℃. After the addition is complete, the mixture is sealed and reacted for 4~24 hours to obtain a mixture of urea-containing imidazole compounds. Under nitrogen or inert gas atmosphere at 0~10℃, a haloalkane is added to the generated mixture of urea-containing imidazole compounds, and the reaction is carried out in a closed system for 24~48h to obtain the urea-containing ionic liquid.

3. The application of the urea-containing ionic liquid according to claim 2 in regulating the elasticity of elastomers, characterized in that, The solvent is at least one selected from acetonitrile, dichloromethane, chloroform, N,N-dimethylformamide, and N,N-dimethyl sulfoxide; The molar ratio of the imidazole compound containing the terminal amino group to the monoisocyanate compound is (0.1~0.3):(0.15~1.5); The dripping time is 0.5~2 hours; The molar ratio of the imidazole compound containing the terminal amino group to the monohaloalkane is (0.1~0.3):(0.2~0.6).

4. The application of the urea-containing ionic liquid according to claim 1 in regulating the elasticity of elastomers, characterized in that, The elasticity of the elastomer is adjusted through the following steps: Step 1: Add the urea-containing ionic liquid to the prepolymer of the elastomer and stir to obtain a mixed solution; or, The elastomer is dissolved in a solvent, and then an ionic liquid containing urea groups is added and stirred to obtain a mixed solution; Step 2: Sonicate the mixed solution obtained in Step 1; Step 3: Pour the ultrasonically treated mixture from Step 2 into the mold, and then heat it with a blower.

5. The application of the urea-containing ionic liquid according to claim 4 in regulating the elasticity of elastomers, characterized in that, The stirring speed is 50~200 rpm, and the stirring time is 24~48h.

6. The application of the urea-containing ionic liquid according to claim 4 in regulating the elasticity of elastomers, characterized in that, The solvent is at least one of N,N-dimethylformamide, butanone, cyclohexanone, acetone, ethyl acetate, toluene, methanol, ethylene glycol, hexafluoroisopropanol, m-cresol, and phenol.

7. The application of the urea-containing ionic liquid according to claim 4 in regulating the elasticity of elastomers, characterized in that, The ultrasonic treatment time is 1 to 4 hours.

8. The application of the urea-containing ionic liquid according to claim 4 in regulating the elasticity of elastomers, characterized in that, The temperature of the blower heating is 60~120℃, and the time is 24~72h.

Citation Information

Patent Citations

  • Carbamido and imidazolium-containing ionic liquid and preparation method thereof

    CN101928250A

  • External cross-linking agent for waterborne polyurethane and preparation method and application of external cross-linking agent

    CN111892694A